Transforming problem-based into project-based learning to enhance social literacy - Rascya Alandra Simbolon; Sintia Ramadani; Nabila Ramadhani Rao; Siti Nayla Rahma Pane (Himpunan Pengembang Kurikulum Indonesia, 2026)
This study is based on the finding that the teaching modules used by tenth-grade Sociology teachers at MAN 2 Model Medan in the 2025/2026 academic year are still dominated by the PBL approach and cooperative learning models, while the learning outcomes of Phase E in the Kurikulum Merdeka require critical thinking competencies up to the creative level (C6). This study aims to analyze the urgency of transitioning from Problem-Based Learning (PBL) to Project-Based Learning (PjBL) to strengthen students' social literacy. This study uses a qualitative descriptive method with a document analysis approach to the teaching modules, annual programs, semester programs, and assessment instruments prepared by the teachers. The analysis results show that the implemented PBL has developed students' analytical skills (C4) but has not fully reached the evaluation (C5) and creative (C6) levels, which are the target learning outcomes. The development of social literacy-based PjBL is formulated as a solution that enables students to produce tangible products through simple social research, thereby authentically strengthening social literacy. Abstrak Kajian ini berangkat dari temuan bahwa modul ajar yang digunakan guru Sosiologi kelas X di MAN 2 Model Medan Tahun Pelajaran 2025/2026 masih didominasi oleh pendekatan PBL serta model-model pembelajaran kooperatif, sementara tuntutan capaian pembelajaran Fase E pada Kurikulum Merdeka menghendaki kompetensi berpikir kritis hingga tingkat mencipta (C6). Penelitian ini bertujuan untuk menganalisis urgensi pengembangan model pembelajaran dari Problem-Based Learning (PBL) menuju Project-Based Learning (PjBL) guna memperkuat literasi sosial murid. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan analisis dokumen (document analysis) terhadap modul ajar, program tahunan, program semester, dan instrumen asesmen yang disusun oleh guru. Hasil analisis menunjukkan bahwa PBL yang diterapkan telah mampu mengembangkan kemampuan analisis (C4) murid, namun belum secara optimal menyentuh level evaluasi (C5) dan kreasi (C6) yang menjadi target capaian pembelajaran. Pengembangan PjBL berbasis literasi sosial dirumuskan sebagai solusi yang memungkinkan murid menghasilkan produk nyata dari penelitian sosial sederhana, sehingga terjadi penguatan literasi sosial secara autentik. Kata Kunci: literasi sosial; problem-based learning; project-based learning; Sosiologi